2022
DOI: 10.1007/s40979-022-00111-2
|View full text |Cite
|
Sign up to set email alerts
|

Proactive learner empowerment: towards a transformative academic integrity approach for English language learners

Abstract: Socializing students to Academic Integrity (AI) in the face of great cultural, linguistic and socioeconomic diversity in the student population in higher education calls for innovative strategies that are aligned with equity, diversity and inclusion principles. Through a mixed method of quantitative analysis of learner engagement data from the Learning Management System (LMS) and analysis of anonymous evaluation survey, along with thematic analysis of students’ open-ended responses in the evaluation survey, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…As such, with the LeD-InF approach, instructors who respond to learners' self-introductions and subsequent academic journal entries communicate genuine empathy, support, and warmth in order to build a relationship of trust and care that enables learners to feel their thoughts are valued and to experience a sense of belonging. An analysis of this approach from the perspective of academic integrity socialization (Khoo and Kang, 2022) showed that opportunities to develop personal connections with academic integrity practice contributed to learners voluntarily writing more than 6,000 words within a month in their co-curricular writing support program. When culturally responsive pedagogy (Gay, 2018) was integrated with the LeD-InF approach, Huo and Khoo (2022) reported that of the 14 low-proficiency learners in their study, eight wrote on average 11,454 words and three wrote on average 6,437 words in one month.…”
Section: Need For Inclusive Learning Opportunitiesmentioning
confidence: 99%
“…As such, with the LeD-InF approach, instructors who respond to learners' self-introductions and subsequent academic journal entries communicate genuine empathy, support, and warmth in order to build a relationship of trust and care that enables learners to feel their thoughts are valued and to experience a sense of belonging. An analysis of this approach from the perspective of academic integrity socialization (Khoo and Kang, 2022) showed that opportunities to develop personal connections with academic integrity practice contributed to learners voluntarily writing more than 6,000 words within a month in their co-curricular writing support program. When culturally responsive pedagogy (Gay, 2018) was integrated with the LeD-InF approach, Huo and Khoo (2022) reported that of the 14 low-proficiency learners in their study, eight wrote on average 11,454 words and three wrote on average 6,437 words in one month.…”
Section: Need For Inclusive Learning Opportunitiesmentioning
confidence: 99%
“…Notably, Reactive Autonomy is a foundational step towards Proactive Autonomy, enabling learners to allocate and manage learning resources independently. Khoo and Kang (2022) state that proactive learners, who engage with the learning process more actively and independently, tend to learn more effectively and exhibit higher motivation levels than their reactive counterparts, who engage more passively.…”
Section: Introduction mentioning
confidence: 99%
“…For example, value statements for DEI have been added to institutional policy (Carter et al., 2022) and programs have been created to promote DEI in colleges and departments (Clark et al., 2021; Marshall et al., 2022). Additionally, curriculum has been altered formally (Henning, 2013; Khoo & Kang, 2022) and informally (Atwater et al., 2013) to include DEI concepts. However, natural science education is still a field in which many students from underrepresented groups may lack a sense of belonging in traditional educational spaces (Campbell et al., 2022; Stoddard, 2022).…”
Section: Introductionmentioning
confidence: 99%